Determination of sodium methylparaben levels in some locally marketed parenteral pharmaceutical products - شرف, نور; فاتن الشب (Latakia University Journal -Medical Sciences Series, 2023)
This study aims to investigate the presence of sodium methylparaben and determine its concentration in some locally marketed pharmaceutical forms. Therefore, we studied 8 ampoules and two oral syrup locally manufactured samples marketed in the Syrian market, packaging and labelling test applied to all samples. The studied samples belonged to sex pharmaceutical companies. The concentration of sodium methylparaben was determined by high-performance liquid chromatography (HPLC) using a column (BDS Hypersil C18 250 mm* 4.6 mm) , mobile phase: methanol as the organic solution with an acetate buffer in the ratio of 82:18, flow rate: 1 ml/minute, UV detection: 254nm. Packaging test revealed that all of the locally manufactured samples matching to WHO guidelines, The results of HPLC analyse showed presence of sodium methylparaben in all studied samples, and all samples were within the allowable limit (0.25% for ampoules, 0.2% for oral syrups) according to the Food and Drug Administration (FDA). The specific concentrations ranged between (1.7-2.28 mg/ml for ampoules and 1.2-1.5 mg/ml for medicinal syrups), depending on the HPLC device.